PELAKSANAAN PENDIDIKAN TASAWUF DI PONDOK PESANTREN AS-SAIDIYYAH 2 BAHRUL ULUM TAMBAKBERAS JOMBANG - Ali Muttaqin (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2020)
ABSTRACT This research analyses the education of Tasawuf at the Islamic Boarding School As-Saidiyyah 2 Bahrul Ulum Jombang. The problems examined in this study are: (1) What are the objectives of Tasawuf education in Islamic boarding schools? (2) What are the materials and how are the methods of Tasawuf education in pesantren? (3) How is the impact of Tasawuf education on the personality of the students in the pesantren? This study used a qualitative approach, the data compilation used observation, interview and documentation analysis about Tasawuf education in the pesantren. While the data analysis used the qualitative analysis model from Miles and Huberman. The results of this research are: First, the purpose of Tasawuf education at As-Saidiyyah 2 Bahrul Ulum Islamic Boarding School is to foster a sense of awareness in students to always think positively, instill noble qualities, always maintain self-purity and always remember Allah, and hope to get pleasure Him in all deeds. Second, the material of Tasawuf that is taught when understood in the perspective of Tasawuf theory is teaching two types of Tasawuf, namely Tasawuf Akhlaki and Amali. Tasawuf akhlaki has a system of building morals through three stages, namely takhalli, tahalli and tajalli. Tasawuf Amali is one's approach to Allah through inclines from one level to a higher level, namely: sharia, thoriqoh, haqiqoh ​​and ma'rifah. While the teaching uses the sorogan, wetonan, wirid ritual, mujahadah, remembering death and habituation of positive behavior in daily life. Third, the impact of Tasawuf education in pesantren is the formation of the personality and noble character of the students. They are aware of the purpose of life and are able to control themselves not to do bad deeds, to obey worship, to be respectful and tawadlu, to grow responsibility, to become a better person and to have a noble character. Keywords: Implementation, Tasawuf Education. ABSTRAK Penelitian ini mengkaji pendidikan tasawuf di Pondok Pesantren As-Saidiyyah 2 Bahrul Ulum Jombang. Permasalahan yang dikaji dalam penelitian ini adalah: (1) Apa saja tujuan pendidikan tasawuf di pesantren? (2) Apa saja materi dan bagaimana metode pendidikan tasawuf di pesantren? (3) Bagaimana dampak pendidikan tasawuf terhadap kepribadian santri di pesantren tersebut? Penelitian ini menggunakan pendekatan kualitatif, penggumpalan datanya menggunakan teknik observasi, wawancara dan analaisis dokumentasi seputar pendidikan tasawuf di pesantren tersebut. Sedangkan analisis datanya menggunakan model analisis kualitatif dari Miles dan Huberman. Hasil penelitian ini adalah: Pertama, Tujuan pendidikan tasawuf di Pondok Pesantren As-Saidiyyah 2 Bahrul Ulum adalah menumbuhkan rasa kesadaraan pada diri santri untuk selau berfikir positif, menanamkan sifat-sifat mulia, selalu menjaga kesucian diri dan selalu mengingat Allah, serta berharap mendapat ridla-Nya dalam semua amal perbuatan. Kedua, materi tasawuf yang diajarkan bila dipahami dalam perspektif teori ilmu tasawuf adalah mengajarkan dua jenis tasawuf, yaitu tasawuf akhlaki dan amali. Tasawuf akhlaki mempunyai sistem pembinaan akhlak melalui tiga tahap, yaitu takhalli, tahalli dan tajalli. Tasawuf amali adalah pendekatakan diri kepada Allah melalui tanjakan dari satu tingkat ke tingkat yang lebih tinggi, yaitu: syariah, thoriqoh, haqiqoh dan ma’rifah. Sedangkan pengajarannya menggunakan metode sorogan, wetonan, ritual wirid, mujahadah, mengingat mati dan pembiasaan perilaku yang positif dalam hidup keseharian. Ketiga, dampak pendidikan tasawuf di pesantren adalah terbentuknya kepribadian dan akhlak mulia santri. Mereka menyadari tujuan hidup dan mampu mengontrol dirinya untuk tidak melakukan perbuatan yang tidak baik, taat beribadah, bersikap hormat dan tawadlu, tumbuhnya tanggungjawab, menjadi sosok yang lebih baik dan berakhlak mulia. Kata Kunci: Pelaksanaan, Pendidikan Tasawuf